Regulation of T lymphocyte subpopulations in specific pathogen-free chickens following experimental fowl adenovirus-ⅧVIII infection - Wang, Chun-jie (Sociedade Brasileira de Microbiologia, 2012)
Two-day-old specific pathogen-free (SPF) chickens were divided into two groups. Group I was inoculated orally with fowl adenovirus Ⅷ (FAV-Ⅷ). Group II served as a negative control. Chickens were investigated at various days post-inoculation (dpi) by flow cytometric analysis for changes in T lymphocyte subpopulations in immune system and blood. In the thymus, CD3(+)T lymphocytes were increased at 25 dpi, with significant increases in the FAV infected noted at 1, 12, 20dpi (p<0.05). This was accompanied by a corresponding increase of CD4(+) and CD8(+) T lymphocytes. In the spleen, CD3(+) and CD4(+) T lymphocytes were increased significantly at 30 dpi (p<0.01) whereas CD8(+) and TCR γ δ(+) T lymphocytes were decreased at 1 (p<0.05), 30 dpi (p<0.01). An increase of CD3(+), CD4(+) and CD8(+) T lymphocytes was noticed in peripheral blood, and accompanied by a decrease of TCR γ δ(+) T lymphocytes. These results demonstrated that infection with FAV-Ⅷ causes significant fluctuations in T lymphocyte subpopulations in thymus, blood and spleen. It can be concluded that an infection with FAV-Ⅷ has profound effects on the immune system, especially on cell mediated immune competency.